2018
DOI: 10.1051/e3sconf/20183401025
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on factors that contribute to the abandonment of building in construction industry in Malaysia

Abstract: Abstract. In Malaysia, the construction sector is one of the important sectors that contribute to economic growth and employments. However, a major concern facing the construction industry is the growing rate of delays in project delivery. In the worse cases, the projects were abandoned due to some reasons when the contract period ended. Abandoned building defines as construction work that has been continuously stalled for 6 months or more, during the project completion period or beyond the scheduled date of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
3
9
0
Order By: Relevance
“…There are many factors that contribute to the abandoned housing project. The main factors are the financial constraints faced by the developer [8]. It is proven since one of the success factor for any development during the implementation phase is the adequate finance [9], [10].…”
Section: Literature Review 21 Factor Contribute To Abandoned Housing ...mentioning
confidence: 99%
“…There are many factors that contribute to the abandoned housing project. The main factors are the financial constraints faced by the developer [8]. It is proven since one of the success factor for any development during the implementation phase is the adequate finance [9], [10].…”
Section: Literature Review 21 Factor Contribute To Abandoned Housing ...mentioning
confidence: 99%
“…3, No. 2, 2020 e-ISSN: 2636 -9419 Finally, the most popular and seemingly perennial genesis of abandoned housing projects in Malaysia is the private developers (Abdul Razak, Abu Samah, & Abdul Wahab, 2016;Ariffin et al, 2018a;Dahlan, 2006;Doraisamy, Akasah, & Yunus, 2014;Hoe, 2013;Khalid, 2010;Mumin & Zainol, 2016;Norhayate et al, 2017;Yusoff, Oseni, & Hasan, 2016). According to Khalid (2010), the developers in the first place are striving to maximize their gains and profits from selling the house.…”
Section: Causes For Abandoned Housing Projects In Malaysiamentioning
confidence: 99%
“…Among those, it was found that the worst scenario in the construction project is the abandoned project. The construction sector in Malaysia has struggled with financial difficulties which have led to many problems associated with abandoned projects [4]. The abandoned housing project in Malaysia is considered as a major problem and need a necessary action to mitigated [5].…”
Section: Revised Manuscript Received On October 22 2019mentioning
confidence: 99%